Authority of religious courts to judge Sharia bankruptcy - Hardyansah, Rommy; Nasution, Krisnadi; Hufron, Hufron; Setyorini, Erny Herlin (Technium Social Sciences Journal, 2022)
At this writing the type of research used, namely the type of normative legal research. Bankruptcy cases in Indonesia have not specifically regulated dealing with Sharia Bankruptcy using sharia principles/sharia contracts. Sharia Bankruptcy Cases are absolutely the competence of the Religious Courts based on the philosophical Aspects, Sociological Aspects, and Juridical Aspects of the Urgency of the Authority of the Religious Courts to Adjudicate Sharia Bankruptcy.